Pengaruh Karakteristik Perusahaan dan Karakteristik Auditor Eksternal terhadap Kecurangan Pelaporan Keuangan - Subroto, Vivi Kumalasari (Jurnal Ilmiah Aset, 2012)
The purpose of this study was to examines the firms characteristics and external audit firms characteristics that influenced the fraudulent financial reporting in Indonesia. The external audit firms characteristics was used as moderating variables for this research. The population of this study was companies in Indonesia. The sample used consisted of fraud firms and non-fraud firms. The number of samples used in this study were 182 companies. The press release reports of Bapepam for 2005-2010 were used to collect data on fraud firms. The samples for non-fraud firms consisted of companies which listed at BEI for 2005-2010. Logistic regression methods were used to test the research hypotheses. The study found that leverage, ROA, change in total assets, financial distress, company age, audit firm tenure, and audit firm’s status were not significantly associated with fraudulent financial reporting.